The 3Rs as a framework to support a 21st century approach for nanosafety assessment. (February 2017) - Burden, Natalie; Aschberger, Karin; Chaudhry, Qasim; Clift, Martin J.D.; Doak, Shareen H.; Fowler, Paul; Johnston, Helinor; Landsiedel, Robert; Rowland, Joanna; Stone, Vicki
Graphical abstract: Highlights: It is timely to consider a paradigm shift in the field of nanosafety. This shift embraces non-traditional approaches that could improve human relevance. The 3Rs provides a framework to support this paradigm shift. There are short, medium and long-term opportunities to align the 3Rs with nanosafety. Key steps needed to enable the paradigm shift are identified. Abstract: Due to the plethora of nanomaterials being manufactured, it is crucial that their effects on human health are understood. It is not feasible to assess the safety of all nanomaterials using animal-based toxicity tests. There are also scientific, business, legislative and ethical drivers to reconsider the use of such toxicity tests. Utilising non-traditional methods has the potential to improve the human relevance of nanosafety assessment, reduce the numbers of animals that are used, and shift the paradigm to a '21st century' approach that exploits recent scientific and technological advances. This article considers how application of the 3Rs principles can be used as a framework to support and guide this paradigm shift in the short, medium and long-term. Bringing the community together to facilitate the transition is necessary to ensure that tangible impacts are made on the efficiency and robustness of the nanosafety assessment process.